81
Пошаговое объяснение:
sina+cosa=-0,9
(sina+cosa)^2=(-0,9)^2
(sina+cosa)^2=0,81
sin^2a+2sinacosa+cos^2a=0,81
(sin^2a+cos^2a)+2sinacosa=0,81
sin^2a+cos^2a=1
2sinacosa=0,81
2sinacosa=sin2a
sin2a=0,81
100sin2a=100*0,81=81
-19
Т.к. sin^2a+cos^2a=1 :
1+2sinacosa=0,81
Т.к. 2sinacosa=sin2a :
1+sin2a=0,81
sin2a=0,81-1
sin2a=-0,19
100sin2a=100*(-0,19)=-19
81
Пошаговое объяснение:
sina+cosa=-0,9
(sina+cosa)^2=(-0,9)^2
(sina+cosa)^2=0,81
sin^2a+2sinacosa+cos^2a=0,81
(sin^2a+cos^2a)+2sinacosa=0,81
sin^2a+cos^2a=1
2sinacosa=0,81
2sinacosa=sin2a
sin2a=0,81
100sin2a=100*0,81=81
-19
Пошаговое объяснение:
Пошаговое объяснение:
sina+cosa=-0,9
(sina+cosa)^2=(-0,9)^2
(sina+cosa)^2=0,81
sin^2a+2sinacosa+cos^2a=0,81
(sin^2a+cos^2a)+2sinacosa=0,81
Т.к. sin^2a+cos^2a=1 :
1+2sinacosa=0,81
Т.к. 2sinacosa=sin2a :
1+sin2a=0,81
sin2a=0,81-1
sin2a=-0,19
100sin2a=100*(-0,19)=-19